2003
DOI: 10.1152/ajpregu.00009.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy changes the muscarinic receptor subtype mediating bladder contraction from M3 toward M2

Abstract: Hypertrophy changes the muscarinic receptor subtype mediating bladder contraction from M3 toward M2. Am J Physiol Regul Integr Comp Physiol 285: R701-R708, 2003. First published May 22, 2003 10.1152/ajpregu.00009.2003.-Major pelvic ganglion electrocautery (MPGE) and spinal cord injury in the rat induce bladder hypertrophy and a change in muscarinic receptor subtypes mediating bladder contraction from predominantly M 3 to a combination of M2 and M3. To determine whether this is a result of bladder hypertrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 25 publications
5
77
1
3
Order By: Relevance
“…In decentralised rat bladders an enhanced and direct contractile role for M 2 has been reported [19]. Similar results were found in obstructed [22] and neurogenic [3,23] rat bladders. The weak M 2 -preference of ABET might then be partially responsible for the increased contractile effects of ABET on ACA in bladders post-SCI, if these bladders indeed have an enhanced M 2 -function.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In decentralised rat bladders an enhanced and direct contractile role for M 2 has been reported [19]. Similar results were found in obstructed [22] and neurogenic [3,23] rat bladders. The weak M 2 -preference of ABET might then be partially responsible for the increased contractile effects of ABET on ACA in bladders post-SCI, if these bladders indeed have an enhanced M 2 -function.…”
Section: Discussionsupporting
confidence: 78%
“…The observed increase in M 2 mRNA is likely to correlate with an elevated expression of M 2 receptors since an increased density of M 2 protein has been reported in decentralised [19], obstructed [22], and neurogenic [23] rat bladders. The behaviour of M 3 mRNA in bladders post-SCI seems to correlate less with the expression of M 3 protein since in hypertrophied [22] and (spontaneous voiding) neurogenic [23] rat bladders a decrease of M 3 protein amount has been reported. Similar noncorrelating findings have been reported before [26] and suggest differences in the cascade from mRNA to protein between M 2 and M 3 .…”
Section: Discussionmentioning
confidence: 79%
“…One group has suggested that M 2 receptors contribute to direct detrusor contraction in the denervated, non-voiding spinal injured rat and the obstructed rat [8,9,27], whilst others could find no evidence of a change in receptor function in the obstructed rat [28]. In the present study patients with neurogenic overactivity due to spinal injury were able to void and in these patients detrusor contraction remained mediated by the M 3 receptor.…”
Section: Discussioncontrasting
confidence: 49%
“…A number of experimental conditions in the rat are associated with an increased contribution of the M 2 receptor subtype to the contractile response. These include sarcoplasmic reticulum calcium depletion with thapsigargin [Braverman et al, 2002], bladder denervation [Braverman et al, 1999;Braverman and Ruggieri, 2003;Ruggieri and Braverman, 2006], spinal cord injury [Braverman et al, 1999], bladder decentralization [Braverman and Ruggieri, 2003], and bladder outlet obstruction [Braverman and Ruggieri, 2003;Ruggieri and Braverman, 2006]. It is unclear if previous bladder hypertrophy, neurogenic lesions, or bladder over activity symptoms were present in the medical history of bladder donors based on the limited information available from the organ procurement agency.…”
Section: Discussionmentioning
confidence: 99%
“…M 2 receptors have been shown to play an indirect role in detrusor contraction by inhibiting bladder smooth muscle relaxation and enhancing detrusor contraction via G i inhibition of cAMP levels [Ehlert et al, 2005]. In pathologic states, the M 2 receptor pathway has a greater role in mediating contraction in rats and humans [Braverman and Ruggieri, 2003;Pontari et al, 2004;Gevaert et al, 2006]. Thus, with pathophysiological stressors, the mechanisms that transduce the muscarinic contractile signal can become altered such that the M 2 receptor subtype plays a more prominent role in the contractile response that is normally mediated by the M 3 receptor subtype.…”
Section: Introductionmentioning
confidence: 99%